Wizualizacja wybranych metod prognozowania z wykorzystaniem programu R - Bartłomowicz, Tomasz (Visualization Methods of Forecasting with the Use of R Computer Programme, 2009)
Time-series methods of forecasting are being used when forecasting is applied to prediction, not to explaining what will happen. The most prognosis methods are programmed but R computer programme does not offer packages containing methods like naive methods of forecasting and others. The article presents R package and procedures which may be used in the research of prognosis with the use of time-series methods of forecasting. The value of the originality of the work relies on: presentation of packages of forecasting procedures in R programming language, validation of R computer programme to forecasting.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 86, s. 165-175